Improved Synthesis of 2',6'-Dihydroxy-3,4-dimethoxy Chalcone by Grinding Technique to Synthesize 5-Hydroxy-3',4'-dimethoxy Flavone - Elfi Susanti VH; Sabirin Matsjeh; Mustofa Mustofa; Tutik Dwi Wahyuningsih (Indonesian Journal of Chemistry, 2014)
5-hydroxy-3',4'-dimethoxy flavone can be efficiently synthesized in two steps via the formation of 2',6'-dihydroxy-3,4-dimethoxy chalcone with good results. 2',6'-dihydroxy-3,4-dimethoxy chalcone as reactants for synthesis of flavones was prepared through Claisen-Schmidt condensation reaction between 2,6-dihydroxyacetophenones,3,4-dimethoxybenzaldehyde and solid NaOH in mortar for 15 min. The yield of the product (70%) is higher than conventional method (65%). This chalcone then oxidatively cyclized with iodine to form 5-hydroxy-3',4'-dimethoxy flavone (yield 62%). Compounds synthesized were characterized by spectroscopic (IR, 1H-NMR, and 13C-NMR).